On Chung’s Law of Large Numbers for Arrays of Extended Negatively Dependent Random Variables - Huang, Haiwu; Yi, Yanchun; Volodin, Andrei; Suraphee, Sujitta (Thailand Statistician, 2021)
In this article, we present some sharp convergence results for partial sums of arrays of rowwise extended negatively dependent random variables. These results are established without assumptions of the identical distribution and stochastic domination. The results generalize and improve the corresponding results of Hu and Taylor (1997), Wu and Zhu (2010), and Wu et al. (2014).